1982
DOI: 10.1002/clc.4960050201
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of the signal averaging technique in clinical cardiology

Abstract: Summary:Since 1963 the signal averaging technique has been applied to improve the signal to noise ratio in highly amplified EKG registrations. Based on the experiences from the literature and the authors own laboratory, the applications of the signal averaging technique in clinical cardiology are reviewed: extraction and analysis of the fetal EKG and P-wave variations, His bundle electrograms from the body surface (recovery rate 33-100% of cases), ventricular delayed depolarizations within the ST segment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 55 publications
2
26
0
1
Order By: Relevance
“…Within the last few years, several investigators have used a noninvasive signal-averaged electrocardiogram (ECG) to detect low-amplitude, high-frequency potentials at the end of the QRS complex in patients with VT. [15][16][17][18][19][20][21][22] These signals, termed "late potentials," appear to correspond to the delayed and fragmented ventricular activation that has been observed with direct electrogram recordings in patients and animals with VT. 15 [23][24][25] Several studies have demonstrated that the signal-averaged ECG can distinguish patients with and without VT after myocardial infarction. '7-22 The purposes of this study were (1) to determine whether the signal-averaged ECG provides information useful in identifying patients with VT that is independent from that which can be obtained from Holter monitoring and catheterization and (2) to determine the combination of findings from the signal-averaged ECGs, cardiac catheterization, and Holter monitoring that best characterize patients with VT after myocardi-DIAGNOSTIC METHODS-ELECTROPHYSIOLOGY al infarction.…”
mentioning
confidence: 99%
“…Within the last few years, several investigators have used a noninvasive signal-averaged electrocardiogram (ECG) to detect low-amplitude, high-frequency potentials at the end of the QRS complex in patients with VT. [15][16][17][18][19][20][21][22] These signals, termed "late potentials," appear to correspond to the delayed and fragmented ventricular activation that has been observed with direct electrogram recordings in patients and animals with VT. 15 [23][24][25] Several studies have demonstrated that the signal-averaged ECG can distinguish patients with and without VT after myocardial infarction. '7-22 The purposes of this study were (1) to determine whether the signal-averaged ECG provides information useful in identifying patients with VT that is independent from that which can be obtained from Holter monitoring and catheterization and (2) to determine the combination of findings from the signal-averaged ECGs, cardiac catheterization, and Holter monitoring that best characterize patients with VT after myocardi-DIAGNOSTIC METHODS-ELECTROPHYSIOLOGY al infarction.…”
mentioning
confidence: 99%
“…The incidence of late potentials within the ST segment has been reported to be around 30-70% of patients with coronary heart disease (Hombach et al, 1980(Hombach et al, , 1982a, depending on the averaging computer used and on the population studied. However, comparative studies on the efficiency of the averaging and the beat-to-beat technique in the same patient have not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…For retrieval of the signal-averaged surface ECG we have used a commercially available signal averaging computer, the MAC-I (Marquette Electronics, Milwaukee, WI), whose performance and reliability have been recently described in detail (Hombach et al, 1980(Hombach et al, , 1982a. The characteristic features of this computer are: A-D sampling rate 4000 samples/s, digital filtering with nearly zero filter ringing, filter ranges DC-300 Hz, 25-300 Hz, 50-300 Hz, 100-300 Hz, trigger unit using a correlation function of 40 samples of the initial 20 ms segment of the QRS complex of all incoming ventricular complexes (trigger stability near k0.2 ms), rejection of ventricular ectopic beats by a pattem-matching technique, averaging window of 600 ms, whose position within the cardiac cycle relative to the trigger point can be changed back or forth by 550 ms, amplification up to 6 x lo* times, maximal number of cycles averaged 8192 beats, analysis of six thoracic leads three bipolar, three augmented).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is considered rather difficult to disclose the precise digitalis effects on it, because the invasive technique is not able to be applied for a long time. More recently, the feasibility of recording His-Purkinje electrograms from the body surface by signal averaging technique has been established (Berbari et af., , 1976Flowers and Horan, 1973;Flowers et al, 1974;Furness et af., 1975;Hishimoto and Sawayama, 1975;Hombach et al, 1982;; Mehra ef af., 1982; Nojima et af., 1985; Rozanski and Castellanos, 1980;Vincent et af. , 1978;Wajszczuk et al, 1978;Yanaga et al 1976).…”
Section: Introductionmentioning
confidence: 99%